China will step up if the US falls behind on climate action - Pey, Peili (2024)
Even under a second Trump administration, climate targets and negotiations will continue, with China stepping up to lead the global energy transition. Southeast Asia must brace itself for protectionist measures from the United States and China, and increased competition between the two in renewable energy.